Biopolymer-surfactant complexes as flow enhancers : characterization and performance evaluation - Mahmood, Wafaa K.; Khadum, Wafaa A.; Eman, E.; Abdulbari, Hayder A. (De Gruyter, 2019)
Artificial polymeric additives are known, and experimentally proven, to be effective drag reducing agents in pipelines with turbulent flow medium. The artificial nature of these additives and their low resistance to high shear forces, exerted by the pipeline geometries and equipment, are considered as major problems against a wider implementation in other industrial applications. The present work introduces a new polymer-surfactant complex of two organic additives (chitosan and sodium laurel ether sulfate, SLES) as a drag reducing agent. The rheological and morphological properties of the new complexes were experimentally tested. The new complex’s drag reduction performance and stability against high shear forces were analyzed using rotating disk apparatus. All the investigated solutions and complexes showed a non-Newtonian behavior. The cryo-TEM images showed a unique polymer-surfactant macrocomplex structure with a nonlinear relationship between its rheological properties and surfactant concentration. A maximum flow enhancement of 47.75% was obtained by the complex (chitosan 300 and 400ppmof chitosan and SLES, respectively) at the rotation speed of 3000 rpm. Finally, the stability of the proposed additives was highly modified when the additive complexes were formed.